2020
DOI: 10.1515/hsz-2020-0345
|View full text |Cite
|
Sign up to set email alerts
|

JMJD3-regulated expression of IL-6 is involved in the proliferation and chemosensitivity of acute myeloid leukemia cells

Abstract: Emerging evidence shows that histone modification and its related regulators are involved in the progression and chemoresistance of multiple tumors including acute myeloid leukemia cells (AML). Our present study found that the expression of histone lysine demethylase Jumonji domain containing-3 (JMJD3) was increased in AML cells as compared with that in human primary bone marrow (HPBM) cells. Knockdown of JMJD3 can decrease the proliferation of AML cells and increase the chemosensitivity of daunorubicin (DNR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Fittingly, Mallaney et al reported that a complete loss of Kdm6b severely impaired HSCs stem cell self-renewal and prolonged survival of MLL-AF9 leukemic mice [ 63 ]. Likewise, KDM6B knockdown re-sensitized AML cell lines to daunorubicin and cytarabine by downregulation of IL6 [ 64 ]. Together, these studies clearly suggest a potential for KDM6B as a drug target in MDS and AML.…”
Section: Resultsmentioning
confidence: 99%
“…Fittingly, Mallaney et al reported that a complete loss of Kdm6b severely impaired HSCs stem cell self-renewal and prolonged survival of MLL-AF9 leukemic mice [ 63 ]. Likewise, KDM6B knockdown re-sensitized AML cell lines to daunorubicin and cytarabine by downregulation of IL6 [ 64 ]. Together, these studies clearly suggest a potential for KDM6B as a drug target in MDS and AML.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed the pivotal role of the cytokine IL-6 in the process of chemotherapeutic resistance [ 17 19 ]. However, no systematic mechanistic investigation has been conducted from a phosphoproteomic perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that elevated levels of serum IL-6 is positively correlated with worse clinical outcomes in patients with different types of cancer, including leukemia [54,55]. IL-6 also plays a key role in the chemoresistance of malignancies [56][57][58]. Based on these findings we checked the effect of our new benzofuran derivatives on IL-6 secretion by K562 cells.…”
Section: Inhibition Of Il-6 Releasementioning
confidence: 97%